2020
DOI: 10.1155/2020/4919154
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Refraction in Myopic Children with and without Atropine Usage

Abstract: Purpose. To compare the patterns of relative peripheral refractions of myopic children who were currently on atropine treatment for myopia control and myopic children who did not use atropine. Methods. Chinese children (n = 209) aged 7 to 12 years participated in the study, 106 used atropine and 103 did not. Participants were also classified into three groups: emmetropes (SE: +0.50 to −0.50 D), low myopes (SE: −0.50 to −3.00 D), and moderate myopes (SE: −3.00 to −6.00 D). The central and peripheral refractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
6
9
0
Order By: Relevance
“…The refraction profile found in this study confirmed a significant hyperopic shift at the peripheral retina in Japanese schoolchildren with mild to moderate myopia. The magnitude of the shift was comparable with that previously reported in myopic children in other counties [7][8][9][10][11][12]. When refractive errors are fully corrected with single-vision spectacles or contact lenses, hyperopic defocus greater than 1 D frequently occurs at the peripheral retina.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The refraction profile found in this study confirmed a significant hyperopic shift at the peripheral retina in Japanese schoolchildren with mild to moderate myopia. The magnitude of the shift was comparable with that previously reported in myopic children in other counties [7][8][9][10][11][12]. When refractive errors are fully corrected with single-vision spectacles or contact lenses, hyperopic defocus greater than 1 D frequently occurs at the peripheral retina.…”
Section: Discussionsupporting
confidence: 86%
“…Table 2 compares RPR at the gaze position of −30 degrees between the current and previous studies conducted in other countries [8][9][10][11][12]. When excluding the results in the mild myopia category from the comparison, the previously Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Fine control of eye-length growth is largely achieved by image processing in the retina [ 7 ], without the need for central/cortical visual processing. The exact mechanism is still a subject of ongoing speculation and investigation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%